Q. 105.0( 4 Votes )

Deduce the Algebraic identity for (x + a) (x + b) (x + c) by using the product formula. [Hint: (x + a) (x + b)(x + c) = (x + a) [(x + b)(x + c)]]

Answer :

Given (x + a)(x + b)(x + c) = (x + a)[(x + b)(x + c)]


(x + a)(x + b)(x + c) = (x + a)[x (x + c) + b(x + c)]


(x + a)(x + b)(x + c) = (x + a)[x2 + cx + bx + bc]


(x + a)(x + b)(x + c) = (x + a)[x2 + x(c + b) + bc]


(x + a)(x + b)(x + c) = x[x2 + x(c + b) + bc] + a[x2 + x(c + b) + bc]


(x + a)(x + b)(x + c) = x3 + x2(c + b) + xbc + ax2 + xa(c + b) + abc


(x + a)(x + b)(x + c) = x3 + x2(a + b + c) + x(ab + bc + ca) + abc


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Discussion on Algebric Identities48 mins
Champ Quiz | Linear Equation in One Variable44 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses